Cop and the Sociologist : Investigating Diversity in German Police Forces. - Thériault, Barbara (Kultur und soziale Praxis., 2013)
Drawing on the sociology of Max Weber, Barbara Thériault investigates today's relations toward difference within German police forces. Accompanying and interviewing police officers whose job it is to contribute to the acknowledgement of difference, the sociologist outlines three ideal types of actors - an empathetic, a principled, and an opportunist one - and the motives underlying their actions. A fourth type, the specialist, is conspicuously absent. Why is that so? Solving this enigma helps depicting the relations to difference within police forces: it points to a specific "spirit" of diversity and a singular way to apprehend the individual in Germany.